Selected nutritional habits of teenagers associated with overweight and obesity - Zalewska,Magdalena; Maciorkowska,Elżbieta (PeerJ, 2017)
Introduction A balanced diet is at the heart of healthy growth and development of children and youth, whereas inappropriate eating habits considerably influence the incidence of disorders connected with nutrition, including overweight and obesity. This paper aims at studying nutritional factors of 18-year-old secondary school youth in the urban environment and their effect on the incidence of overweight and obesity. Materials and methods The survey was conducted among 1,999 secondary school students chosen at random. The research tool consisted an original survey questionnaire. The measurements of respondents’ height and body mass provided data for calculating the body mass index. Results and conclusion The percentage of youth with deficient body mass was estimated at 8.4%. The percentage of normal weight students in the surveyed group was estimated at 77.6%. Overweight and obesity characterized 14.0% of the total number. As many as 21.8% of overweight and obese respondents would eat one or two meals as opposed to 16.8% of normal weight students. Three-fourths of the surveyed students would eat breakfast regardless of their nutritional habits. Lunch is eaten by 52.9% of normal weight 18-year-olds and 46.1% of overweight and obese students. The analysis of mealtimes suggests that overweight and obese students would have their breakfast and dinner at later hours than the rest of the surveyed. More than half of the participating students failed to eat lunch (53.9%), and one in four students within this group resigned from supper. Girls would eat fruit and vegetables more frequently than boys several times a day. The percentage of persons in the surveyed groups who would eat fast foods on a daily basis was similar regardless of their nutritional status. Sweetened carbonated beverages would be drunk more often by overweight and obese boys (81.2%) as compared with boys with proper body mass (75.8%). The same type of beverages would be popular with two-thirds of girls, and this result was similar regardless of their nutritional status. About 44.2% of overweight and obese girls and 20% of girls with proper body mass attempted to lose weight, and 5.7% of boys tried to go on a diet. Eating limitations were declared by 16.5% of overweight and obese boys and ca. 3% of normal weight boys. Conclusion Within the surveyed group of youth, it was possible to indicate eating errors primarily consisting in irregular eating, too low a number of meals during the day, particularly skipping breakfast, which took place more frequently among overweight and obese students rather than normal weight ones. The survey points to the insufficient intake of vegetables and fruit as opposed to salty and sweet meals. It is essential to convey the knowledge on the causes of overweight and obesity as well as rules of a healthy diet as factors preventing civilization diseases.
Keywords: Nutritional habits; Diet; Youth; Overweight and obesity